2017
DOI: 10.1016/j.jcs.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ozone treatment on the molecular properties of wheat grain proteins

Abstract: Ozone is a powerful and highly reactive oxidizing agent, which has found increasing applications in the field of grain processing. However, in some cases, O3 can potentially promote oxidation and/or degradation of the chemical constituents of grains. Experiments were carried out to evaluate the specific effects of gaseous ozone on the molecular properties of wheat grain proteins and their consequences on the bread-making quality of the resulting flours.Ozonation causes a significant reduction in the SDS solubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Prolonged high‐concentration ozone exposure led to the degradation of the gluten structure through oxidation, which might explain the lower protein content in treated wheat grain. The causative role of protein oxidation is supported by previous studies . After ozone treatment with 2.44 g m −3 for up to 7.79 h, it was observed that the 1000‐kernel weight of treated grain, as compared to untreated grain, was reduced and that the hardness was increased.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…Prolonged high‐concentration ozone exposure led to the degradation of the gluten structure through oxidation, which might explain the lower protein content in treated wheat grain. The causative role of protein oxidation is supported by previous studies . After ozone treatment with 2.44 g m −3 for up to 7.79 h, it was observed that the 1000‐kernel weight of treated grain, as compared to untreated grain, was reduced and that the hardness was increased.…”
Section: Resultssupporting
confidence: 59%
“…22,23 Trombete et al 24 reported the effect of ozone on chemical properties, mineral profile and rheological properties of wheat at an ozone concentration of 60 mg L −1 and found no significant alteration due to treatment. Gozé et al 25 observed no significant changes in wheat starch when treated with ozone gas at a flow rate of 33.34 L min −1 for up to 60 min, but in their previous study, 26 changes in rheological properties in flour samples were reported, implying oxidation of protein and non-starch polysaccharides as possible reasons. Gozé et al 27 studied the effect on the molecular structure of wheat protein after exposure to ozone at concentrations varying from 60 to 180 g m −3 Normal temperature and pressure and noticed a decrease in the amount of -helix and -pleated structures.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, due to its oxidizing properties, ozone can promote changes in the constituents of wheat (GOZÉ et al, 2017). Ozone can partially demolish the cell structure (ZOU et al, 2015) and oxidize carotenes, tannins, ascorbates, flavoproteins or polyphenols and other constituents (OBADI et al, 2017).…”
Section: Introductionmentioning
confidence: 99%